New species of Bacuma Cameron (Hymenoptera: Braconidae: Braconinae) from Kenya and West Darfur with a key to species - Quicke, Donald L. J.; Guy, Travis J.; Noort, Simon Van; Broad, Gavin R.; Butcher, Buntika A. (Zootaxa, 2017)
Three new species of the Afrotropical braconine wasp genus Bacuma are described, and biological observations (nectar feeding) by one of them are noted. The new species are: B. kayserae Quicke & Butcher sp. nov. from Kenya, B. madiensis Quicke & Butcher sp. nov. from Uganda and B. darfurensis Quicke & Butcher sp. nov. from Sudan. A group of four large nominal species with red metasomas and finely sculptured tergites (B. granulatus, B. maculipennis, B. rufa and B. whitei) may represent a single widespread species or a pair of species separated by mesoscutum colour, or four separate but morphologically very similar species. However, given the small number of specimens available for study and the poor condition of some of these, including the types, they are not formally synonymised here. A partial key to the species of Bacuma is presented, which recognizes those species that are clearly distinct, including three new species. Interactive Lucid dichotomous and matrix keys are available on www.waspweb.org.